Feeding dynamics and distribution of the hyperiid amphipod, Themisto gaudichaudii (Guérin, 1828) in the polar frontal zone, Southern Ocean - Lange, Louise (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2006)
The population structure and feeding dynamics of the hyperiid amphipod, Themisto gaudichaudii, was investigated during two cruises of the South African National Antarctic Programme conducted in the Indian sector of the Polar Frontal Zone during austral autumn (April) 2004 and 2005. During the 2004 cruise the frontal features that delimit the PFZ converged to form a single distinctive feature. In 2005, the research cruise was conducted in the vicinity of a cold-core eddy which was spawned from the Antarctic Polar Front. Total mesozooplankton abundance and biomass during the 2004 study ranged from 55.19 to 860.57 ind. mâ »Â³, and from 2.60 to 38.42 mg dwt mâ »Â³, respectively. In 2005 the abundance and biomass ranged from 23.1 to 2160.64 ind. mâ »Â³, and from 0.76 to 35.16 mg dwt mâ »Â³, respectively. The mesozooplankton community was numerically dominated by copepods, pteropods, and ostracods during both surveys. The abundance and biomass of Themisto gaudichaudii in the region of investigation was < 0.2 ind. mâ »Â³ (range 0.01 to 0.15 ind. mâ »Â³) and < 0.06 mg dwt mâ »Â³ (range 0.02 to 0.06 mg dwt mâ »Â³) during 2004, while in 2005 the abundance and biomass of the amphipod ranged from < 0.01 to 0.2 ind. mâ »Â³ and < 0.01 to 0.04 mg dwt mâ »Â³, respectively. These values correspond to < 1% of the total mesozooplankton abundance and biomass during both surveys. T. gaudichaudii exhibited no significant spatial patterns in abundance, biomass and total length during both 2004 and 2005 (p > 0.05 in all cases). A key feature of the two investigations was the virtual absence of juveniles (total length < 15 mm) among the amphipod population, supporting the suggestion that they exhibit strong seasonal patterns in reproduction. Gut content analysis during both years indicated that for both the male and female amphipods', copepods were the most prevalent prey species found in stomachs, followed by chaetognaths and pteropods. Results of electivity studies indicate that T. gaudichaudii is an opportunistic predator, generally feeding on the most abundant mesozooplankton prey. Results of in vitro incubations indicated that the total daily feeding rate of T. gaudichaudii during 2004 ranged from 11.45 to 20.90 ind. mâ »Â³ dâ »Â¹, which corresponds to between 0.12 and 1.64% of the total mesozooplankton standing stock. In 2005, the feeding rate ranged between 0.1 and 1.73% of the total mesozooplankton standing stock. The low predation impact of T. gaudichaudii during this study can be related to their low abundances and high interannual variability throughout the region of investigation.
Keywords: Themisto gaudichaudii -- Antarctic Ocean; Hyperiidae -- Antarctic Ocean; Zooplankton -- Antarctic Ocean